Uso dos materiais curriculares por professores de Matemática - Bueno, Simone (2017)
In this research, at the doctoral level, we aim to investigate how the curricular materials are used by teachers of Mathematics. The work is characterized by qualitative research. The data were collected from the fieldwork, the material of analysis and observation of the classes of four teachers of Mathematics, in a public school, focusing on the posture of the teacher when using the curricular materials. In order to understand the relationship between teachers and curricular materials, we use the Brown (2009) study, which highlights the resources on each side of the relationship and points out the different types of use: reproduction, adaptation and creation. Complementing our referential, we seek authors who talk about curriculum, Pires (2004, 2008, 2011, 2012), Shulman (1986) and Sacristán (2000). Regarding the factors that influenced teachers in the use of curricular materials, we consider that training, participation in courses after graduation, trust in content, pedagogical knowledge of the subject and collaboration are factors that may have contributed to the way That teachers differed in the use of their materials. In the interactions of the teachers with the curricular materials, we could perceive that in some moments the teachers reproduced, in others they adapted and in the same class improvised. We consider that the results of this research can join to others and contribute to understand what use the teacher makes of the curricular materials and what impacts these materials have in their practice when working in mathematical learning situations